CONCEPTUAL BASES OF CORPORATE SECURITY OF THE ENTERPRISES (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The history of the emergence and development of corporations has long historical roots, but in Ukraine only the first steps have been taken, which are designed to contribute to the spread of this most effective form of business organization. The advantages of the corporate form of organization of business activities, along with the strengthening of globalization processes, motivates representatives of domestic business to prefer corporations. Taking advantage of the corporation’s competitive advantage is possible provided its corporate security at the proper level. Today, there are only a few definitions of the term “corporate security”, and theoretical and methodological approaches, methodological foundations and practical recommendations are in the formative stage. The own definition of corporate security as an activity aimed at achieving mutually agreed corporate interests through the effective use of available resources and protection from the negative impact of threats, makes it possible to create safe conditions for the sustainable development of the enterprise. Borrowing foreign corporate security is impossible due to significantly different business conditions. Solving the problem of ensuring corporate security requires first of all an awareness of its essence, determining the range of tasks and determining the possibility of achieving it. The conceptual framework for ensuring corporate security in Ukrainian enterprises in the following set was determined and substantiated: protection of the rights and interests of shareholders; parity balance of interests of all stakeholders; transparency of corporate governance; awareness of the financial and economic status and results of the company; protection of property and interests of the corporation; sound management proper corporate control over the enterprise; effective use of corporate resources; high corporate culture; Social responsibility. The application of the conceptual framework should contribute to the formation of a corporate security system in the conditions of each enterprise, which would take into account the actual conditions of the national economy and reduce the likelihood of the negative impact of key external and internal threats. The gradual approximation of the national practice of the functioning of corporations with the standards of countries with developed economies will allow maximum use of the advantages of corporations with a reduction of their shortcomings.